Revisiting the Cretaceous Mancos Group in Utah—problems, previous methods, and new perspectives on a world-class Cretaceous marine section (Geology of the Intermountain West, 2025)
The Mancos Group is an upper Cenomanian-middle Campanian lithostratigraphic unit that records large-scale changes in sedimentation patterns associated with the incursion of the Western Interior seaway across western Colorado into central Utah. Understanding the stratigraphic relationships in this unit is of critical scientific importance to understanding marine stratigraphic sequences across the globe. This field trip focuses on synonymizing units into consistent lithostratigraphic packages in the framework of biostratigraphy and currently available geochronology. Field trip stops emphasize the hierarchical division of each Mancos unit, the information present/absent for correlation, and fossil occurrences and how they relate to paleoenvironment and index fauna, as well as disparate sedimentological characteristics (grainsize, bioclastic content, glauconite abundance, cementation).